2017
DOI: 10.1167/17.9.20
|View full text |Cite
|
Sign up to set email alerts
|

L-/M-cone opponency in visual evoked potentials of human cortex

Abstract: L and M cones send their signals to the cortex using two chromatic (parvocellular and blue-yellow koniocellular) and one luminance (magnocellular) pathways. These pathways contain ON and OFF subpathways that respond to excitation increments and decrements respectively. Here, we report on visually evoked potentials (VEP) recordings that reflect L- and M-cone driven increment (LI and MI) and decrement (LD and MD) activity. VEP recordings were performed on 12 trichromats and four dichromats (two protanopes and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Recently, L- and M-cone opponent processing has been demonstrated to affect perceived brightness ( 7 ), the flicker ERG ( 8 , 9 ), and VEPs at occipital scalp locations ( 10 ). In all these parameters, selective increments of L-cone illuminance are encoded as brightness increments, whereas M-cone increments are encoded as brightness decrements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, L- and M-cone opponent processing has been demonstrated to affect perceived brightness ( 7 ), the flicker ERG ( 8 , 9 ), and VEPs at occipital scalp locations ( 10 ). In all these parameters, selective increments of L-cone illuminance are encoded as brightness increments, whereas M-cone increments are encoded as brightness decrements.…”
Section: Discussionmentioning
confidence: 99%
“…This method has recently been used to show that selective decrements in M-cone illuminance are paradoxically perceived as brightness increments ( 7 ). M-cone square-wave modulations furthermore produce electroretinogram (ERG) traces that are in opposite phase with traces resulting from L-cone (or L+M-cone) modulations ( 8 , 9 ), which has also been shown in visually evoked potentials (VEPs) recorded at occipital scalp locations ( 10 ). Thus, at different levels of visual processing, M-cone increments are perceived as brightness decrements, whereas L-cone increments and L+M increments are perceived as brightness increments.…”
mentioning
confidence: 99%
“…Color vision loss and demyelinating disorders such as optic neuritis have been linked with retinal axonal loss visible in OCT imaging 9,14 and to increased error scores and N-wave latencies in VEP waveforms. [15][16][17][18][19] The players' baseline OCT scans, however, revealed that retina, optic nerve head, and ganglion cell complex anatomy are within normal, healthy limits (data not shown and Bixenmann et al 9 ). This suggests that the players' red/green differences are due to optic nerve or retinal dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…While cortical processing is essential for the perception of color, it may not be essential for physiological VEP response. 15,16 Because our players have significant differences in their VEP responses, upper-level visual cortex is not involved but rather simple processing or dysfunction in the lateral geniculate nucleus (LGN) may be responsible for observed differences between red and green. We cannot completely rule out upperlevel involvement, though, because color perception involves multiple areas across a hierarchy of regions interacting with each other in a complex, recursive manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation